Coating solution for lithium-ion battery, lithium-ion battery separator and lithium-ion battery

By applying coatings of nanowires and ceramic powder on the lithium-ion battery separator, the problems of insufficient thermal stability, puncture resistance and electrolyte wetting are solved, and performance improvement is achieved without increasing thickness and weight.

CN114361715BActive Publication Date: 2024-12-24SHENZHEN SENIOR TECH MATERIAL
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202111662828.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2018-08-31
Publication Date
2024-12-24
Estimated Expiration
2038-08-31

AI Technical Summary

Technical Problem

The existing lithium-ion battery separators have problems such as poor thermal stability, poor puncture resistance and poor electrolyte wetting, which limits their application in batteries.

Method used

Nanowires, ceramic powder and adhesives are mixed into a coating liquid, applied to the surface of the diaphragm and cured to form a coating layer, which improves the thermal stability, puncture resistance and electrolyte wetting properties of the diaphragm.

Benefits of technology

It effectively solves the problems of insufficient thermal stability, puncture resistance and electrolyte wetting properties of the diaphragm, while avoiding the thickness and weight increase caused by excessive coating, achieving good performance improvement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003450125840000111
    Figure BDA0003450125840000111
  • Figure BDA0003450125840000112
    Figure BDA0003450125840000112
Patent Text Reader

Abstract

The present invention discloses a coating liquid for a lithium-ion battery separator, a lithium-ion battery separator and a lithium-ion battery. The raw materials of the coating liquid include: nanowires, ceramic powder, adhesive and solvent; the nanowires are at least one of nanocellulose, carbon nanotubes, nanosilver wires, boron carbide nanowires, copper hydroxide nanowires, aramid nanofibers, silicon monoxide nanowires and hydroxyapatite nanowires; the diameter of the nanowires is 1 to 100 nm and the length is 0.1 to 100 μm; the ceramic powder is at least one of aluminum oxide, silicon oxide, titanium oxide, boehmite and attapulgite. The present invention uses nanowires, ceramic powder and adhesive to mix to obtain a coating liquid, which is applied to the surface of the separator body and cured to obtain a lithium-ion battery separator composed of a separator body and a coating loaded on the separator body. The lithium-ion battery separator has good thermal stability and puncture resistance.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the invention patent application with application number 201811015292.0 filed on August 31, 2018 and invention name “Coating liquid for lithium-ion batteries, lithium-ion battery separator and lithium-ion battery”. Technical Field

[0002] The present invention relates to the technical field of lithium ion batteries, and in particular to a coating liquid for lithium ion batteries, a lithium ion battery separator and a lithium ion battery. Background Art

[0003] Lithium-ion batteries have been widely used in portable electronic devices such as mobile phones, cameras, and laptops due to their high specific energy, high operating voltage, long cycle life, no memory effect, low self-discharge, pollution-free, green and environmentally friendly, and long cycle life. They are also listed as candidate power sources for electric vehicles, aerospace, military, and large energy storage equipment. With the development of lithium-ion batteries, the requirements for battery capacity, high and low temperature resistance, and cycle life are getting higher and higher. Lithium-ion batteries are currently a widely used secondary battery.

[0004] Lithium-ion batteries are mainly composed of four major materials, including positive electrode materials, negative electrode materials, separators, and electrolytes. As one of its important components, the separator plays a very important role in its performance. The separator refers to a layer of separator material between the positive and negative electrodes of the battery, usually referred to as a battery separator. The main function of the battery separator is to isolate the positive and negative electrodes and prevent the electrons in the battery from passing freely, while allowing the ions in the electrolyte to pass freely between the positive and negative electrodes.

[0005] The ion conductivity of the battery separator is directly related to the overall performance of the battery. Its function of isolating the positive and negative electrodes can limit the increase of current when the battery is overcharged or the temperature rises, preventing the battery from short-circuiting and causing explosion. It has a micropore self-closing protection function, which plays a role in safety protection for battery users and equipment.

[0006] Polyolefin materials are widely used as microporous separators due to their low price, good mechanical strength and chemical stability, good comprehensive performance and low cost. However, their poor thermal stability, poor puncture resistance and poor electrolyte wettability limit their further application in batteries. Summary of the invention

[0007] In view of this, the present invention provides a coating liquid for lithium ion batteries, a lithium ion battery separator and a lithium ion battery, which better overcome the problems and defects of the above-mentioned prior art. The present invention uses a coating liquid obtained by mixing nanowires, ceramic powders and adhesives, etc., and applies it on the surface of the separator body, and solidifies it to obtain a lithium ion battery separator composed of a separator body and a coating loaded on the separator body. The lithium ion battery separator has good thermal stability, puncture resistance, electrolyte wettability and mechanical strength, etc., and effectively solves the problems of poor thermal stability, poor puncture resistance and poor electrolyte wettability of the existing separator.

[0008] A coating liquid for lithium-ion battery separator, the raw materials of the coating liquid comprising: nanowires, ceramic powder, adhesive and solvent;

[0009] The nanowire is at least one of nanocellulose, carbon nanotube, nanosilver wire, boron carbide nanowire, copper hydroxide nanowire, aramid nanofiber, silicon monoxide nanowire and hydroxyapatite nanowire; the nanowire has a diameter of 1 to 100 nm and a length of 0.1 to 100 μm;

[0010] The ceramic powder is at least one of aluminum oxide, silicon oxide, titanium oxide, boehmite and attapulgite, and the particle size of the ceramic powder is 5 to 1000 nm.

[0011] Furthermore, the mass ratio of the ceramic powder to the nanowire is (0.1-5):1; the mass of the nanowire accounts for 1-30% of the mass of the solvent; and the mass of the adhesive accounts for 1-50% of the mass of the solvent.

[0012] Furthermore, the raw materials of the coating liquid also include: an auxiliary agent; the mass of the auxiliary agent accounts for 0.01 to 3% of the mass of the solvent.

[0013] Furthermore, the adhesive is at least one of polyvinyl alcohol, polyacrylonitrile, polyacrylic acid, styrene-butadiene rubber, carboxymethyl cellulose, polyvinylidene fluoride, polyvinyl pyrrolidone and polyimide; and the solvent includes at least one of water, ethanol, acetone and N-methylpyrrolidone.

[0014] Furthermore, the auxiliary agent is at least one of fluoroalkyl ethoxy alcohol ether, fatty alcohol polyoxyethylene ether, sodium butylbenzene naphthalene sulfonate, sodium hydroxyethyl sulfate and sodium dodecyl sulfate.

[0015] The present invention also provides a lithium ion battery separator, comprising a separator body and a coating loaded on the separator body, wherein the coating is obtained by coating and curing at least one side surface of the separator body with the above-mentioned coating liquid.

[0016] Furthermore, the coating method is dip coating, spray coating, spin coating or blade coating.

[0017] Furthermore, the diaphragm body is a polypropylene microporous membrane, a polyethylene microporous membrane or a polypropylene / polyethylene microporous membrane; and the thickness of the diaphragm body is 3 to 20 μm.

[0018] Furthermore, the coating has a thickness of 0.01 to 1 μm.

[0019] The present invention also provides a lithium ion battery, which comprises the lithium ion battery separator.

[0020] Compared with the prior art, the coating liquid for lithium ion batteries, lithium ion battery separator and lithium ion battery of the present invention have the following beneficial effects:

[0021] The present invention uses a coating liquid obtained by mixing nanowires, ceramic powders and adhesives to coat the surface of the diaphragm body and solidify it to obtain a lithium-ion battery diaphragm composed of a diaphragm body and a coating loaded on the diaphragm body. The lithium-ion battery diaphragm has good thermal stability, puncture resistance, electrolyte wettability and mechanical strength, etc., and effectively solves the problems of poor thermal stability, poor puncture resistance and poor electrolyte wettability of existing diaphragms; further, the nanowires and ceramic powders used in the coating materials of the lithium-ion battery diaphragm can avoid the problem of thick coatings leading to increased thickness and weight of the entire diaphragm, thereby achieving the lithium-ion battery diaphragm with good thermal stability, puncture resistance and electrolyte wettability, and small increase in thickness and weight.

[0022] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are given below for detailed description as follows. DETAILED DESCRIPTION

[0023] In order to facilitate the understanding of the present invention, the technical solution of the present invention is described in detail below in combination with embodiments. In the following description, many specific details are elaborated to facilitate a full understanding of the present invention.

[0024] However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific implementation disclosed below.

[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. In the event of a conflict, the definitions in this specification shall prevail.

[0026] As used herein:

[0027] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0028] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0029] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0030] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0031] A coating liquid for lithium ion battery separator, the raw materials of the coating liquid comprising: nanowires, ceramic powder, adhesive and solvent.

[0032] It should be noted that the aspect ratio of the nanowire (i.e. the ratio of length to diameter) must be greater than 50. For example, the aspect ratio of the nanowire can be 100, 500, 1000, 8000 or 10000; the diameter of the nanowire is 1 to 100 nm, such as 1 nm, 5 nm, 10 nm, 20 nm, 30 nm, 50 nm, 80 nm or 100 nm; the length of the nanowire is 0.1 to 100 μm, such as 0.1 μm, 0.5 μm, 1 μm, 5 μm, 10 μm, 30 μm, 50 μm, 80 μm or 100 μm.

[0033] The nanowire is at least one of nanocellulose, carbon nanotube, nanosilver wire, boron carbide nanowire, copper hydroxide nanowire, aramid nanofiber, silicon monoxide nanowire and hydroxyapatite nanowire.

[0034] The ceramic powder is at least one of aluminum oxide, silicon oxide, titanium oxide, boehmite and attapulgite. The particle size of the ceramic powder is 5 to 1000 nm, such as 5 nm, 10 nm, 50 nm, 80 nm, 100 nm, 300 nm, 500 nm, 800 nm or 1000 nm.

[0035] Preferably, the mass ratio of the ceramic powder to the nanowires is (0.1-5):1, such as 0.1:1, 0.5:1, 1:1, 2:1, 3:1, 4:1 or 5:1, etc.; the mass of the nanowires accounts for 1-30% of the mass of the solvent, such as 1%, 5%, 8%, 10%, 15%, 20%, 25% or 30%, etc.; the mass of the adhesive accounts for 1-50% of the mass of the solvent, such as 1%, 5%, 10%, 20%, 30%, 40% or 50%, etc.

[0036] Preferably, the raw materials of the coating liquid also include: an auxiliary agent; the mass of the auxiliary agent accounts for 0.01-3% of the mass of the solvent, such as 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5% or 3%.

[0037] It should be noted that when an auxiliary agent is added to the raw materials of the coating liquid, it is helpful to improve the surface tension of the coating liquid on the surface of the base film such as the polyolefin microporous membrane.

[0038] Preferably, the adhesive is at least one of polyvinyl alcohol, polyacrylonitrile, polyacrylic acid, styrene-butadiene rubber, carboxymethyl cellulose, polyvinylidene fluoride, polyvinyl pyrrolidone and polyimide; and the solvent includes at least one of water, ethanol, acetone and N-methylpyrrolidone.

[0039] Preferably, the auxiliary agent is at least one of fluoroalkyl ethoxy alcohol ether, fatty alcohol polyoxyethylene ether, sodium butylbenzene naphthalene sulfonate, sodium hydroxyethyl sulfate and sodium dodecyl sulfate.

[0040] The present invention also provides a method for preparing a coating liquid, wherein the coating liquid is the above-mentioned coating liquid, and the preparation method comprises: uniformly mixing various raw materials.

[0041] Preferably, the preparation method comprises: first dispersing the long nanowires and the short nanowires in a solvent, stirring or ultrasonically mixing them uniformly, then adding an adhesive, and continuing to stir or ultrasonically mix them uniformly to obtain a coating liquid. Furthermore, an auxiliary agent may be added after adding the adhesive.

[0042] The present invention also provides a lithium ion battery separator, comprising a separator body and a coating loaded on the separator body, wherein the coating is obtained by coating and curing at least one side surface of the separator body with the above-mentioned coating liquid.

[0043] Preferably, the coating method can be dip coating, spray coating, spin coating, roller coating or blade coating, etc. The curing method can be radiation curing or UV curing or heating and drying in an oven for curing. Preferably, the curing temperature is 40°C to 100°C, such as 40°C, 50°C, 60°C, 70°C, 80°C, 90°C or 100°C, etc., and the curing time is 5 to 120s, such as 5s, 10s, 30s, 50s, 80s, 100s or 120s, etc.

[0044] It should be noted that the above coating can be obtained by coating the coating liquid on one side surface of the diaphragm body (the side facing a certain electrode) or on both sides surface of the diaphragm body (the two sides facing the two electrodes), and then curing; it depends on actual needs.

[0045] Preferably, the diaphragm body is a polypropylene microporous membrane, a polyethylene microporous membrane or a polypropylene / polyethylene microporous membrane. It should be noted that the polypropylene microporous membrane, the polyethylene microporous membrane or the polypropylene / polyethylene microporous membrane are all commercially available products, for example, they can be made by a dry stretching process.

[0046] Preferably, the thickness of the diaphragm body is 3-20 μm, such as 3 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm or 20 μm.

[0047] Preferably, the coating has a thickness of 0.01 to 1 μm, such as 0.01 μm, 0.05 μm, 0.08 μm, 0.1 μm, 0.3 μm, 0.5 μm, 0.8 μm or 1 μm.

[0048] It should be noted that the nanowires in the coating liquid form the main skeleton of the coating, so that the diaphragm has good mechanical strength. The composite ceramic powder further enables the diaphragm to have good puncture resistance and electrolyte infiltration properties.

[0049] The present invention uses a coating liquid obtained by mixing nanowires, ceramic powders and adhesives to coat the surface of the diaphragm body and solidify it to obtain a lithium-ion battery diaphragm composed of a diaphragm body and a coating loaded on the diaphragm body. The lithium-ion battery diaphragm has good thermal stability, puncture resistance, electrolyte wettability and mechanical strength, etc., and effectively solves the problems of poor thermal stability, poor puncture resistance and poor electrolyte wettability of existing diaphragms; further, the nanowires and ceramic powders used in the coating materials of the lithium-ion battery diaphragm can avoid the problem of thick coatings leading to increased thickness and weight of the entire diaphragm, thereby achieving the lithium-ion battery diaphragm with good thermal stability, puncture resistance and electrolyte wettability, and small increase in thickness and weight.

[0050] The present invention also provides a lithium ion battery, which comprises the lithium ion battery separator.

[0051] In order to facilitate the understanding of the present invention, the technical scheme of the present invention is further described below in conjunction with embodiments. The applicant declares that the present invention illustrates the detailed process equipment and process flow of the present invention through the following embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention should rely on the following detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, the equivalent replacement of the raw materials of the product of the present invention, the addition of auxiliary components, the selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

[0052] Example 1

[0053] (1) 27 parts of ceramic powder and 30 parts of nanowires are dispersed in 100 parts of ethanol, stirred and mixed evenly, and then 50 parts of styrene-butadiene rubber are added to the mixture, and the mixture is stirred and mixed evenly to obtain a coating liquid; wherein the nanowires are carbon nanotubes with a diameter of 1 to 100 nm and a length of 0.1 to 100 μm, and the ceramic powder is attapulgite with a particle size of 100 nm.

[0054] (2) The coating liquid prepared in step (1) is uniformly coated on one side of the polyethylene microporous membrane by spraying, and then cured at 70°C for 50s; and then cooled to room temperature to obtain a lithium ion battery separator composed of a polyethylene microporous membrane and a coating loaded on the surface of the polyethylene microporous membrane, wherein the thickness of the polyethylene microporous membrane is 20 μm, and the thickness of the coating is 0.05 μm.

[0055] Example 2

[0056] (1) 7.5 parts of ceramic powder and 15 parts of nanowires are dispersed in 100 parts of ethanol, stirred and mixed evenly, and then 25 parts of polyvinyl alcohol are added to the mixture, and the stirring and mixing are continued to obtain a coating liquid; wherein the nanowires are nanocellulose with a diameter of 1 to 100 nm and a length of 0.1 to 100 μm, and the ceramic powder is aluminum oxide with a particle size of 500 nm.

[0057] (2) The coating liquid prepared in step (1) is uniformly coated on one side of the polyethylene microporous membrane by spraying, and then cured at 40°C for 120s; then cooled to room temperature to obtain a lithium ion battery separator composed of a polyethylene microporous membrane and a coating loaded on the surface of the polyethylene microporous membrane; wherein the thickness of the polyethylene microporous membrane is 10 μm, and the thickness of the coating is 0.3 μm.

[0058] Example 3

[0059] (1) Dispersing 1 part of long nanowires and 10 parts of short nanowires in 200 parts of ethanol, stirring and mixing them evenly, then adding 15 parts of polyvinyl alcohol to the mixture, continuing to stir and mix evenly, to obtain a coating solution; wherein the nanowires are hydroxyapatite nanowires with a diameter of 1 to 100 nm and a length of 0.1 to 100 μm, and the ceramic powder is aluminum oxide with a particle size of 1000 nm.

[0060] (2) The coating liquid prepared in step (1) is uniformly coated on one side of the polyethylene microporous membrane by spraying, and then cured at 90°C for 10s; then cooled to room temperature to obtain a lithium ion battery separator composed of a polyethylene microporous membrane and a coating loaded on the surface of the polyethylene microporous membrane; wherein the thickness of the polyethylene microporous membrane is 5 μm, and the thickness of the coating is 1 μm.

[0061] Example 4

[0062] (1) 2 parts of ceramic powder and 10 parts of nanowires are dispersed in 100 parts of ethanol, stirred and mixed evenly, and then 12 parts of polyvinyl alcohol and 0.1 parts of sodium dodecyl sulfate are added to the mixture, and the mixture is stirred and mixed evenly to obtain a coating solution; wherein the nanowires are carbon nanotubes with a diameter of 1 to 100 nm and a length of 0.1 to 100 μm, and the ceramic powder is attapulgite with a particle size of 200 nm.

[0063] (2) The coating liquid prepared in step (1) is uniformly coated on one side of the polyethylene microporous membrane by spraying, and then cured at 60°C for 80s; then cooled to room temperature to obtain a lithium ion battery separator composed of a polyethylene microporous membrane and a coating loaded on the surface of the polyethylene microporous membrane; wherein the thickness of the polyethylene microporous membrane is 8 μm, and the thickness of the coating is 0.5 μm.

[0064] Example 5

[0065] (1) 6 parts of ceramic powder and 10 parts of nanowires are dispersed in 50 parts of ethanol, stirred and mixed evenly, and then 15 parts of polyvinyl alcohol and 0.5 parts of sodium dodecyl sulfate are added to the mixture, and the mixture is stirred and mixed evenly to obtain a coating solution; wherein the nanowires are carbon nanotubes with a diameter of 1 to 100 nm and a length of 0.1 to 100 μm, and the ceramic powder is attapulgite with a particle size of 300 nm.

[0066] (2) The coating liquid prepared in step (1) is uniformly coated on one side of the polyethylene microporous membrane by spraying, and then cured at 80°C for 30s; then cooled to room temperature to obtain a lithium ion battery separator composed of a polyethylene microporous membrane and a coating loaded on the surface of the polyethylene microporous membrane; wherein the thickness of the polyethylene microporous membrane is 12 μm, and the thickness of the coating is 0.1 μm.

[0067] Example 6

[0068] (1) 8 parts of ceramic powder and 10 parts of nanowires are dispersed in 40 parts of ethanol, stirred and mixed evenly, and then 16 parts of adhesive and 1.2 parts of sodium dodecyl sulfate are added to the mixture, and the mixture is stirred and mixed evenly to obtain a coating solution; wherein the nanowires are carbon nanotubes with a diameter of 1 to 100 nm and a length of 0.1 to 100 μm, and the ceramic powder is attapulgite with a particle size of 600 nm.

[0069] (2) The coating liquid prepared in step (1) is uniformly coated on one side of the polyethylene microporous membrane by spraying, and then cured at 50°C for 100s; then cooled to room temperature to obtain a lithium ion battery separator composed of a polyethylene microporous membrane and a coating loaded on the surface of the polyethylene microporous membrane; wherein the thickness of the polyethylene microporous membrane is 18 μm, and the thickness of the coating is 0.05 μm.

[0070] Example 7

[0071] The difference between this embodiment and embodiment 4 is that 4 parts of ceramic powder and 10 parts of nanowires are dispersed in 100 parts of ethanol, and the rest is the same as embodiment 4.

[0072] Example 8

[0073] The difference between this embodiment and embodiment 4 is that 6 parts of ceramic powder and 10 parts of nanowires are dispersed in 100 parts of ethanol, and the rest is the same as embodiment 4.

[0074] Example 9

[0075] The difference between this embodiment and embodiment 4 is that 8 parts of ceramic powder and 10 parts of nanowires are dispersed in 100 parts of ethanol, and the rest is the same as embodiment 4.

[0076] Example 10

[0077] The difference between this embodiment and embodiment 4 is that 3 parts of ceramic powder and 15 parts of nanowires are dispersed in 100 parts of ethanol, and the rest is the same as embodiment 4.

[0078] Embodiment 11

[0079] The difference between this embodiment and embodiment 4 is that 4 parts of ceramic powder and 20 parts of nanowires are dispersed in 100 parts of ethanol, and the rest is the same as embodiment 4.

[0080] Example 12

[0081] The difference between this embodiment and embodiment 4 is that 6 parts of ceramic powder and 30 parts of nanowires are dispersed in 100 parts of ethanol, and the rest is the same as embodiment 4.

[0082] The thermal stability, puncture resistance and contact angle of the coating surface of the lithium ion battery separator prepared in the above embodiments 1 to 12 were tested, and lithium ion batteries were made using the lithium ion battery separator prepared in the above embodiments 1 to 12, and their electrical properties were tested. The test results are shown in Table 1 below.

[0083] Among them, the thermal stability of the diaphragm is measured in accordance with GB / T 21650.1-2008 standard;

[0084] Puncture resistance: measured in accordance with GB / T 36363-2018 standard.

[0085] Table 1

[0086]

[0087]

[0088] In Table 1, the batteries in Examples 1 to 12 and Comparative Examples 1 to 3 have the same main structure, including a positive electrode, a negative electrode, an electrolyte and a separator, wherein the lithium ion battery separators in Comparative Examples 1 to 2 differ from those in Examples 1 to 12 in that the coating is thicker; the lithium ion battery separator in Comparative Example 3 is a polyethylene microporous membrane, and no substance used to form the coating is loaded. It should be noted that the above polyethylene microporous membranes are all commercially available products.

[0089] As can be seen from Table 1 above, the contact angles of the coating surfaces of the lithium ion battery separators obtained in the coating solutions prepared in Examples 1 to 12 are smaller than the contact angles of the lithium ion battery separators of Comparative Example 3 due to the addition of auxiliary agents; the contact angles of the coating surfaces of the lithium ion battery separators obtained in the coating solutions prepared in Examples 4 to 12 due to the addition of auxiliary agents are smaller than the contact angles of the coating surfaces of the lithium ion battery separators prepared in Examples 1 to 3. It should be noted that the same effect can be achieved by replacing the auxiliary agents in the coating solutions prepared in Examples 4 to 12 with at least one of fluoroalkyl ethoxy alcohol ethers, fatty alcohol polyoxyethylene ethers, sodium butylbenzene naphthalene sulfonate and sodium hydroxyethyl sulfate.

[0090] In summary, by using the lithium-ion battery separator provided by the embodiment of the present invention, the thermal stability, puncture resistance and electrolyte wettability of the lithium-ion battery separator are significantly improved, and at the same time, the battery capacity retention rate of the battery is improved to a certain extent.

[0091] It should be noted that the same effect as above can be achieved by replacing the diaphragm bodies in the above Examples 1 to 12, ie, Comparative Examples 1 to 3, with polypropylene microporous membranes or polypropylene / polyethylene microporous membranes.

[0092] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the formula and preparation process of the present invention may be subject to various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A lithium ion battery separator, characterized in that: It comprises a diaphragm body and a coating loaded on the diaphragm body, wherein the coating is obtained by coating and curing at least one side of the diaphragm body with a coating liquid, wherein: The raw materials of the coating liquid include: nanowires, ceramic powder, adhesive and solvent; The nanowire is at least one of nanocellulose and carbon nanotube; the diameter of the nanowire is 1 to 100 nm and the length is 0.1 to 100 μm; The ceramic powder is at least one of aluminum oxide, silicon oxide, titanium oxide, boehmite and attapulgite, and the particle size of the ceramic powder is 5 to 1000 nm; The mass ratio of the ceramic powder to the nanowire is (0.1-0.9):1; The thickness of the coating is 0.01 to 0.8 μm; The raw materials of the coating liquid also include: an auxiliary agent; the mass of the auxiliary agent accounts for 0.1 to 3% of the mass of the solvent.

2. The lithium-ion battery separator according to claim 1, characterized in that: The mass ratio of the ceramic powder to the nanowire is (0.1-0.5):1; the mass of the nanowire accounts for 1-30% of the mass of the solvent; and the mass of the adhesive accounts for 1-50% of the mass of the solvent.

3. The lithium-ion battery separator according to claim 1, characterized in that: The adhesive is at least one of polyvinyl alcohol, polyacrylonitrile, polyacrylic acid, styrene-butadiene rubber, carboxymethyl cellulose, polyvinylidene fluoride, polyvinyl pyrrolidone and polyimide; the solvent includes at least one of water, ethanol, acetone and N-methylpyrrolidone.

4. The lithium-ion battery separator according to claim 1, characterized in that: The auxiliary agent is at least one of fluoroalkyl ethoxy alcohol ether, fatty alcohol polyoxyethylene ether, sodium butylbenzene naphthalene sulfonate, sodium hydroxyethyl sulfate and sodium dodecyl sulfate.

5. The lithium-ion battery separator according to claim 1, characterized in that: The coating method is dipping, spraying, spin coating, roller coating or blade coating.

6. The lithium ion battery separator according to claim 1, characterized in that: The diaphragm body is a polypropylene microporous membrane, a polyethylene microporous membrane or a polypropylene / polyethylene microporous membrane; the thickness of the diaphragm body is 3-20 μm.

7. A lithium ion battery, characterized in that: The lithium ion battery comprises the lithium ion battery separator according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Lithium ion battery ceramic diaphragm paste

    CN105489819A

  • Ceramic diaphragm and preparation method and application thereof

    CN105529425A

  • Sol-coated membrane and preparation method and use thereof

    CN108155326A

  • Pottery coating lithium ion battery diaphragm

    CN205723722U